Mastering Kali Linux for advanced penetration testing : a practical guide to testing your network's security with Kali Linux, the preferred choice of penetration testers and hackers /: a practical guide to testing your network's security with Kali Linux, the preferred choice of penetration testers and hackers. (2014) - Beggs, Robert W
No abstract available